2021
DOI: 10.1002/ptr.7324
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide: A review of its pharmacology, pharmacokinetics, toxicity and clinical trials and pharmaceutical researches

Abstract: Andrographis paniculata (Burm. f.) Wall. ex Nees, a renowned herb medicine in China, is broadly utilized in traditional Chinese medicine (TCM) for the treatment of cold and fever, sore throat, sore tongue, snake bite with its excellent functions of clearing heat and toxin, cooling blood and detumescence from times immemorial. Modern pharmacological research corroborates that andrographolide, the major ingredient in this traditional herb, is the fundamental material basis for its efficacy. As the main component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 224 publications
(142 reference statements)
2
43
0
Order By: Relevance
“…In contrast to the results from a trial of Xiyanping from which andrographolide was given as an intravenous route and significant recovery was found in an active group, ( 11 ) our results were from oral administration of AP. Although there is no direct comparison study of the efficacy of AP in different dosage forms, it has been shown that andrographolide has a poor oral bioavailability (<3%) primarily due to undergoing rapid metabolism at duodenal and jejunal cells ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the results from a trial of Xiyanping from which andrographolide was given as an intravenous route and significant recovery was found in an active group, ( 11 ) our results were from oral administration of AP. Although there is no direct comparison study of the efficacy of AP in different dosage forms, it has been shown that andrographolide has a poor oral bioavailability (<3%) primarily due to undergoing rapid metabolism at duodenal and jejunal cells ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the results from a trial of Xiyanping from which andrographolide was given as an intravenous route and significant recovery was found in an active group, (11) our results were from oral administration of AP. Although there is no direct comparison study of the efficacy of AP in different dosage forms, it has been shown that andrographolide has a poor oral bioavailability (<3%) primarily due to undergoing rapid metabolism at duodenal and jejunal cells (17). ¶ Worsening symptoms were the composite of receiving antiviral drugs, systemic corticosteroids, or ventilator support; having oxygen saturation drop along with worsening signs and symptoms; or presenting regressive chest X-ray findings (i.e., category three or above).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Although there is no direct comparison study of the efficacy of AP in different dosage forms, it has been shown that andrographolide has a poor oral bioavailability (<3%) primarily due to undergoing rapid metabolism at duodenal and jejunal cells. (17)…”
Section: Discussionmentioning
confidence: 99%
“…The results of a randomized controlled trial of 44 patients showed that andrographolide in the treatment of multiple sclerosis showed a trend to reduce the rate of brain atrophy and disability progression, but andrographolide had adverse events of rash and dysgeusia ( Ciampi et al, 2020 ). Some people have pointed out that their nephrotoxicity and reproductive toxicity are more common ( Zeng et al, 2022 ). In terms of hepatotoxicity, from the application of andrographolide in liver diseases, we can find that andrographolide has a good repairing effect on hepatotoxicity, but there is no evidence that it can induce liver damage.…”
Section: Safety Testing Of Andrographolide and Its Derivativesmentioning
confidence: 99%